The Role of Early Upbringing of Children on Their Later Academic Achievements in Western Division, Tororo Municipality - Akware Irene Violet (Uganda Christian University, 2025)
Upbringing of children has and continues to be one of the most challenging tasks of or times. Irrespective of its relationship to academic performance, the traditional modes of child upbringing have been curtailed. This study explored the role of early upbringing of children on their later academic achievements in Western Division, Tororo Municipality. Specifically, the study explored the various ways of upbringing children and the role of early upbringing of children on their later academic achievements in Western Division, Tororo Municipality. The study also determined appropriate interventions of early upbringing of children in Western Division, Tororo Municipality. The study used qualitative research approach and a case study design of 25 participants who include parents, teachers and pupils in primary schools were interviewed. Data was collected from participants using interview method. Study findings revealed that authoritarian upbringing is one of the ways through which children can be brought up. Others ways included authoritative, permissive and uninvolved upbringing. Findings also revealed that parents suffering from financial hardship are more likely to care about making ends meet rather than raising their children and children from divorced families have few chances for educational success. It is also that parent-child age differences influence achievements. The study also discovered that upbringing environment determines access and success in schooling. Additionally, the findings of the study revealed that improving behavioral Discipline Practices as a measure and utilizing the power of role models may help to enhance early upbringing of children as well as improving physical health and safety of children will help to address gaps in early upbringing of children. The study recommended that government and stakeholders should sensitize the community of the most appropriate ways of early child upbringing and put in place measures that enhance academic performance of all children irrespective of family background. Other recommendation implementing a range of mechanisms and strategies, there is need to strengthen child rights protection by government and stakeholders in family systems.